THE EFFECT OF PEER EDUCATION ON IMPROVING STUDENT KNOWLEDGE IN PREPARATION FOR THE INDONESIAN NURSE COMPETENCY EXAMINATION - Nirwanto K Rahim; Ita Sulistiani (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2026)
Introduction: The Indonesian Nurse Competency Examination (INCE) remains a critical requirement for nursing graduates; however, fluctuating pass rates indicate persistent gaps in student preparedness. Innovative, scalable strategies are needed to enhance learning outcomes. Peer education, grounded in social learning theory, offers a potentially effective approach to improving knowledge and exam readiness. This study aimed to evaluate the effect of peer education on student knowledge in preparation for the INCE.Methods: A pre-experimental one-group pretest–posttest design was conducted over 10 days involving 53 nursing professional students selected through total sampling. Knowledge was measured using a structured try-out instrument aligned with INCE competency domains. Paired t-tests were used to assess differences in pre- and post-intervention scores.Results: At baseline, only 41.1% (n = 23) of students achieved the passing threshold, while 58.9% (n = 33) did not meet the standard. Following the intervention, the proportion of students who passed increased substantially to 91.9% (n = 51), with only 8.9% (n = 5) remaining below the threshold, representing an absolute increase of 50.8 percentage points. Mean knowledge scores improved significantly from 46.16 ± 6.41 at baseline to 52.41 ± 5.48 post-intervention, with a mean difference of 6.25 points (p < 0.001). This finding indicates not only statistical significance but also a meaningful educational impact.Conclusion: Peer education is an effective, low-cost, and scalable strategy for enhancing student knowledge in INCE preparation. Its integration into structured mentoring programs may strengthen competency-based education and contribute to improving national examination outcomes.